2010
DOI: 10.1007/s11661-009-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Glass-Forming Ability and Competitive Crystalline Phases for Lightweight Ti-Be–Based Alloys

Abstract: The glass-forming ability (GFA) for the Ti-Be-based alloys in the Ti-Be-Zr ternary system is systematically studied. It was found that the best GFA obtained at a composition of Ti 41 Be 34 Zr 25 (at. pct) in the Ti-Be-Zr ternary system, and the bulk-metallic-glass (BMG) rod samples with a diameter of 5 mm were fabricated by Cu-mold casting. The competitive crystalline phases around the composition of the best GFA materials were determined by scanning electron microscopy (SEM) and X-ray diffractometry (XRD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…Without containing heavy late transition metals (e.g., Cu, Ni, and Fe), the density of these alloys was lower than 5 g/cm 3 , resulting in a high specific strength larger than 400 J/g, which is more than twice that of the commercial Ti-6Al-4V (the most widely used crystalline titanium alloy). In 2010, Zhang et al systematically studied the GFA of the Ti-Zr-Be system [80,81]. As shown in Figure 6, two amorphous regions were found in the Ti-Zr-Be system.…”
Section: Be-containing Ti-bmgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without containing heavy late transition metals (e.g., Cu, Ni, and Fe), the density of these alloys was lower than 5 g/cm 3 , resulting in a high specific strength larger than 400 J/g, which is more than twice that of the commercial Ti-6Al-4V (the most widely used crystalline titanium alloy). In 2010, Zhang et al systematically studied the GFA of the Ti-Zr-Be system [80,81]. As shown in Figure 6, two amorphous regions were found in the Ti-Zr-Be system.…”
Section: Be-containing Ti-bmgsmentioning
confidence: 99%
“…Therefore, Be-bearing Ti-based BMGs exhibit relatively low density and high specific strength compared with Be-free Ti-based BMGs. Moreover, as the atomic radius of Be is much smaller than that of most metallic atoms (as shown in Table 1), it has been found that the addition of Be significantly improves the GFA of Zr- [118,119], Cu- [120], and Ti-based BMGs [79][80][81]. Except for the Ti-Cu-Ni system mentioned in Section 2.1.1, the Ti-Zr-Be system is another important Ti-based ternary system with bulk glass-forming ability.…”
Section: Be-containing Ti-bmgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, a TiZr-based BMG with a maximum size of over 50 mm has been reported by Tang et al [13]. High Zr content in this alloy, however, dramatically increases its density and thus reduces its specific strength compared to those high Ti containing BMGs [14,15]. Driven by the desire to further lower the cost and enhance the specific strength, developing new Ti-based BMGs with excellent GFA is thus meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Therefore, extensive research has been conducted in the Ti-rich corner of the (Zr,Ti)-(Cu,Ni)-Be pseudoternary glass-forming system, [11,12] and only recently, low density Ti-Zr-Be-based BMGs with improved specific strength excluding LTMs (e.g., Fe, Ni, Cu, and Sn) have been developed. [13,14] These results imply that the adjustment of the LTM content in alloys of the Vitreloy series allows tailoring of the yield strength while still maintaining a large specific strength. [15] On the other hand, plasticity is also a desirable property for BMGs for widespread practical application.…”
Section: Introductionmentioning
confidence: 89%